حوكمة المسؤولية الاجتماعية للمؤسسات الصغيرة والمتوسطة- " العـــــــــــــلاقة والأهــــــــــــــمية" - بن أحمد, أحمد (جامعة الوادي - University of Eloued, 2022)
تعتبر المؤسسات الصغيرة والمتوسطة من أهم المؤسسات في الدولة بمختلف جوانبها، وهي تمثل الركيزة الأساسية للاقتصاد الوطني من خلال مساهمته في تحقيق الأهداف التنموية والاقتصادية والاجتماعية، وبالتالي فهي تساهم وبشكل كبير في توفير فرص عمل وتنويع الهياكل الصناعية وجذب المدخرات المحلية وترقية الصادرات ورفع القيمة المضافة للاقتصاد الوطني بصفة عامة، ولتحقيق التنمية الاقتصادية يجب على المؤسسات الصغيرة والمتوسطة الاهتمام بالمسؤولية الاجتماعية بمختلف اتجاهات محيطها سواءا كان خارجيا أو داخليا على حد سواء، وباعتبار أن الدولة هي المسؤول الوحيد عن برامج التنمية الاجتماعية، لذا أصبح من الضروري تطبيق قواعد ومحددات وآليات حوكمة المؤسسات بإعتبارها أحد المصطلحات التي تتقيد وترتبط بمفهوم المسؤولية الاجتماعية للمؤسسات بشكل كبير The SME is one of the most important institutions in the country in all its aspects. It represents the main pillar of the national economy through its contribution to the achievement of the economic, social and development goals, thus contributing significantly to the creation of employment opportunities, diversification of industrial structures, attracting domestic savings, In general. To achieve economic development, small and medium enterprises must take social responsibility into the various directions of their environment, both externally and internally, and considering that the State is solely responsible for Bram C´ Social development. It is therefore necessary to apply the rules, determinants and mechanisms of corporate governance as one of the terms that are closely related to the concept of CSR
Corporate Social Responsibility Governance for Small and Medium Enterprises - Relationship and Importance -
مقال
Keywords: الحوكمة، المسؤولية الاجتماعية، المؤسسات الصغيرة والمتوسطة.; Governance, Social Responsibility, Small and Medium Enterprises.